Factores biosocioculturales y nivel de información sobre el cuidado del recien nacido a término en primigestas, Moche 2013 - Nieto Polo Salinas, Maria Susana (2013)
This descriptive correlational research was carried out with primigravida, in order to determine the relation of biosocioculturales factors: age, education level, marital union and area of origin and level of information on care of the newborn at term of primigravida attending the Maternal and Child Health Center Santa Lucia de Moche, 2013. The sample universe consisted of 68 primigravida, to which they applied the test of "Level of information about newborn care term." The results were processed in SPSS version 19 and presented in simple tables and double numerical frequencies and percentages. For statistical analysis we applied the chisquare test of independence of criteria, with a significance level of five percent. The results show that 55.9 percent of first pregnancies studied are older than 20 years, 45.6 percent have a superior- instruction grade, 69.1 percent haven’t a partner, 60.3 percent come from the rural area and 54.4 percent of first pregnancies have a hushed information level, results show relation between factors of age and area of origin with the level of information about care of the newborn at term of the primigravida.